THE RELATION BETWEEN VERBAL AND VISUAL EXPRESSIONS IN SANDERS AND DEMICCOâ€™S â€œTHE CROODS 1â€ - Saputra, Muhammad Ari; Sutopo, Djoko (Universitas Negeri Semarang, 2016)
Communication is generally defined as having both a verbal and nonverbal component. Verbal communication often refers to the words we use in communication whereas nonverbal communication refers to communication that is produced by some means other than words (eye contact, body language, or vocal cues) (Knapp & Hall, 2009:5). This study describes the relation between verbal and visual expression in â€œThe Croods 1â€. The aims of this study are to describe how verbal relate to visual expression in â€œThe Croods 1â€. There are six of facial expressions relate to visual expression and language features relate to verbal expression. The facial blueprints of the major emotions-how surprise, fear, disgust, anger, happiness and sadness are registered by changes in the forehead, eyebrows, eyelids, cheeks, nose, lips, and chin. This research used descriptive method with qualitative approach. The object of this research was â€œThe Croods 1â€. There are 30 data of facial expression were identified in the movie. They are 5 data in surprise expression, 6 data in fear expression, 3 data in disgust expression, 6 data in anger expression, 7 data in happiness expression and 3 data in sadness.Hence, there are relations between verbal and visual expression in â€œThe Croods 1â€. The researcher would like to give some suggestions about the analysis of dialogs in a film using semiotic approach such as used Ferdinand approach, Barthes approach, and Eco approach and so on.